Prenatal Maternal Stress Associated with ADHD and Autistic Traits in early Childhood - Ronald, Angelica; Pennell, Craig E.; Whitehouse, Andrew J. (Frontiers in Psychology, 2011)
Research suggests that offspring of mothers who experience high levels of stress during pregnancy are more likely to have problems in neurobehavioural development. There is preliminary evidence that prenatal maternal stress (PNMS) is a risk factor for both autism and ADHD, however most studies do not control for confounding factors and no study has investigated PNMS as a risk factor for behaviors characteristic of these disorders in early childhood. A population cohort of 2900 pregnant women were recruited before their 18th week of pregnancy and investigated prospectively. Maternal experience of stressful life events was assessed during pregnancy. When offspring were age 2-years, mothers completed the Child Behavior Checklist. Multiple regression showed that maternal stressful events during pregnancy significantly predicted ADHD behaviours in offspring, after controlling for autistic traits and other confounding variables, in both males (p= .03) and females (p= .01). Similarly, stressful events during pregnancy significantly predicted autistic traits in the offspring after controlling for ADHD behaviours and confounding variables, in males only (p= .04). In conclusion, this study suggests that PNMS, in the form of typical stressful live events such as divorce or a residential move, show a small but significant association with both autistic traits and ADHD behaviours independently, in offspring at age 2 years, after controlling for multiple antenatal, obstetric, postnatal and sociodemographic covariates. This finding supports future research using epigenetic, cross-fostering, and gene-environment interaction designs to identify the causal processes underlying this association.